Nitrate in lettuce and ion mobility in soil fertilized with urban waste compost - Mantovani, José Ricardo; Ferreira, Manoel Evaristo; da Cruz, Mara Cristina Pessôa (Pesquisa Agropecuaria Brasileira, 2005)
Environmental contamination by nitrate due to the agricultural use of urban waste compost has been poorly studied. The objective of this work was to evaluate the effect of urban waste compost on nitrate accumulation in lettuce, on nitrate mobility in soil and on nitrate losses by leaching, in two successive cultivations. Two simultaneous experiments were carried out in greenhouse, in PVC columns, in randomized blocks design, with five treatments and four replicates. In one of them a lettuce cultivation was carried out and in the other one, two sucessive cultivations. The treatments were five urban waste compost rates, equivalents to 0, 30, 60, 90 and 120 t ha-1. Columns were filled with soil from depths of 0–20 (treated with waste compost), 20–40 and 40–60 cm of a medium texture Ultisol, and one lettuce seedling. Urban waste compost does not turn the lettuce inappropriate to be consumed due to the nitrate concentration but it is of potential risk to the contamination of the groundwater due to nitrate leaching.
Keywords: Lactuca sativa; nitrogen; leaching